Możliwości usuwania WWA ze ścieków w procesach fizyczno-chemicznych = Removal of PAHs from wastewater in the physical and chemical processes - Smol, Marzena; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a review of the literature on the application of physical and chemical processes for removal of PAHs from wastewater. The Polish legislation conditions for PAHs in wastewater and effectiveness of chemical oxidation, photodegradation, sorption and membrane processes in the degradation or removal of these micropollutants were described.
Keywords: WWA; utlenianie; fotoutlenianie; sorpcja; procesy membranowe; PAHs; oxidation; photo-oxidation; sorption; membrane processes